Vida cotidiana e habitação de interesse social em Morrinhos: uma perspectiva de análise para a (re)produção do espaço urbano - (:unkn) unknown (Universidade Federal de Goiás, 2016)
This paper aims to understand the (re)production of the urban space of Morrinhos, state of Goias, Brazil, starting with the Social Housing Project (SHP) and the social relations consubstantiated and exposed on the everyday life of the residents. The specific goals are: to learn about the organization of urban space of Morrinhos, based on historical, economical and social conditions; to read the general conditions of the housing of the aforementioned city, and elucidate part of the intentionalities of the housing policies in Brazil as an important part for the process of (re)production of urban space and; lastly, to meet several components of the everyday life of a few SHP residents in areas such as Monte Verde, Bela Vista I and Bela Vista II, in Morrinhos, and, thus, to assess part of the assumptions that are related to the socio-spatial reproduction of these localities. The methodological procedures were based on theoretical research, especially in bibliographic sources that debate the (re)production of urban space, housing and everyday life. In the documental research, the public domain data, especially the ones from Morrinhos, were organized; regarding the field research, a semistructured interview script was used to SHP residents, and observation were registered on the field journal and photographic records in the selected areas for empirical research. The present study reveals that everydayness is a characteristic of the researched residents, i.e. the objective and subjective attainment of the residents decreases their creative potentiality and determine them to the fragmentation of life in spheres, such as in the work environment, private life, leisure etc, purposely unarticulated of the social reality as a whole. Thereby, the urban space of Morrinhos reproduces inhumanely, so that the resident contemplated with a SHP becomes a reduced subject to the labor force condition and also as a consumer. Such strangeness overlaps the feeling of belonging to the class, which legitimates, thus, the entire process of reproduction of capital and space.
Everyday life and social housing project of Morrinhos: an analysis of the (re)production of urban space
Keywords: (Re)production; Urban space; Housing; Everyday life; resident; (Re)produção; Espaço urbano; Habitação; Vida cotidiana; Morador; GEOGRAFIA HUMANA::GEOGRAFIA URBANA